Identification of a Novel Genotype of Hepatitis G Virus in Southeast Asia - Naito, Hideo (American Society for Microbiology, 1999)
Hepatitis G virus (HGV) isolates obtained from 20 Myanmarese and 10 Vietnamese subjects were analyzed. A cluster of isolates not belonging to any known genotype of HGV was found in five Myanmarese subjects and three Vietnamese subjects by phylogenetic analysis, and we classified this new genotype as type 4. These results revealed that the HGV genome can be classified into at least four major genotypes.